Concurrent production of carotenoids and lipid by a filamentous microalga Trentepohlia arborum. (August 2016) - Chen, Lin; Zhang, Lanlan; Liu, Tianzhong
Highlights: T. arborum could simultaneously synthesize high amounts of carotenoids and lipid. Carotenoids (mainly β -carotene) accounted for ca . 5% in the microalgal lipid. First report of lipid and fatty acid accumulation characteristics in T. arborum . Abstract: During the study of Trentepohlia arborum it became clear that its cells are rich in lipids and carotenoids. Thus, lipid content, composition and fatty acids profiles in individual lipid classes, as well as pigment profiles, responding to different culture conditions, were further investigated. The results showed that the predominant carotenoids and lipid fraction in total lipid in this study was β -carotene and TAG, respectively. The lipid content increased significantly under high light while nitrogen-replete conditions induced the highest carotenoids content. However, only with a double stress of high light and nitrogen-deficiency it was possible to maximize the productivities of both carotenoids and lipids. Carotenoids (mainly β -carotene) accounted for ca . 5% of the microalgal lipid under the double stress. Data herein show the potential of T. arborum for the production of both lipids and carotenoids, and hence provide an appropriate way to produce different products from T. arborum .